Wireless power transfer through metal using inductive link - Vu, Tuan Anh; Pham, Chi Van; Pham, Anh-Vu; Gardner, Christopher S. (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
This paper presents a highly efficient power transfer system based on a co-design of a class-E power amplifier (PA) and a pair of inductively coupled Helical coils for through-metal-wall power transfer. Power is transferred wirelessly through a 3.1-mm thick aluminum barrier without any physical penetration and contact. Measurement results show that the class-E PA achieves a peak power gain of 25.2 dB and a maximum collector efficiency of 57.3%, all at 200 Hz. The proposed system obtains a maximum power transfer efficiency of 9% and it can deliver 5 W power to the receiver side through the aluminum barrier.